The Palgrave Handbook of International Development 2016
DOI: 10.1057/978-1-137-42724-3_24
|View full text |Cite
|
Sign up to set email alerts
|

The Violence of Development: Guerrillas, Gangs, and Goondas in Perspective

Abstract: This chapter analyses the intuitively compelling assumption that violence is inimical to development. Ever since Marx argued that the development of Europe proceeded through "primitive accumulation", many writers from a wide range of theoretical perspectives have in fact regarded development as inherently reliant on coercion and force. The chapter provides a brief survey of arguments that violence is linked with development before outlining three examplesthe cases of guerrillas, gangs and goondas-that, we argu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…As Robert Bates (2001), Gareth A. Jones and Dennis Rodgers (2016) have highlighted, it is by no means proven that peace is a necessary pre-condition for prosperity, and the occupational trajectories of former barrio Luis Fanor Hernández gang members highlight how under certain circumstances violence can constitute a major comparative advantage for individuals, sometimes even their main one. Seen in this way, if the point of a DDR programme is to provide assistance to former combatants and enable them to find jobs, including starting their own businesses, then perhaps the most efficient way to achieve this is to allow them to maximize their violence expertise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Robert Bates (2001), Gareth A. Jones and Dennis Rodgers (2016) have highlighted, it is by no means proven that peace is a necessary pre-condition for prosperity, and the occupational trajectories of former barrio Luis Fanor Hernández gang members highlight how under certain circumstances violence can constitute a major comparative advantage for individuals, sometimes even their main one. Seen in this way, if the point of a DDR programme is to provide assistance to former combatants and enable them to find jobs, including starting their own businesses, then perhaps the most efficient way to achieve this is to allow them to maximize their violence expertise.…”
Section: Resultsmentioning
confidence: 99%
“…Leaving aside for now the thorny question of the relationship between security and development (see Bates 2001;Jones and Rodgers 2016;Jensen 2010), and focusing instead on the violence-reducing function of DDR programmes, this can generally be said to be underpinned by certain basic assumptions. These include, in particular, the notion that 'former combatants face unique and specific challenges' -in that they have a lack of usable skills and may be suffering from trauma -and that 'targeted reintegration programmes are necessary', which need to be specifically adapted to permit beneficiaries to overcome barriers such as stigma and discrimination linked to their combatant role (Barron 2009: 255).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, scholars have examined the criminal governance practices of gangs, such as their governance over populations within a specific territory (Arias 2014;Campana and Varese 2018;Levitt and Venatesh 2000;Lessing and Willis 2019;Skarbek 2011;Wolff 2015). Previous research has shown how gangs tend to govern areas where they are physically based and where the power of the state presence is weak (Arias and Goldstein 2010;Campana and Varese 2018;Hume 2004;Levitt and Venatesh 2000;Koonings and Kruijt 1999;Jones and Rodgers 2016). For example, Arias (2014) argues that gangs can exploit opportunities to operate as "parallel" or "alternative sources" of political and economic power where the state has limited presence or limited legitimacy.…”
Section: Gangs and Criminal Governancementioning
confidence: 99%
“…Previous research has shown how gang members often act-or promise to do so-in predictable ways, which can be in contrast to the actions of the state, which, in the community's perception, appears to act in an arbitrary fashion (Jones and Rodgers 2016). As an example, in Nicaragua, Rodgers (2006) explored how gangs complied with a cardinal "golden rule" not to harm local inhabitants; the victims of local gangs were outsiders.…”
Section: Gangs and Criminal Governancementioning
confidence: 99%
“…However, despite these, there appears to be sparse mention of third place / space specifically in relation to gangs and education. and creativity (Ferrell, 1996;Borden, 2010;Edensor et al, 2012 in Jorgensen andKeenan, 2012), projected tele-visualised space (Baudrillard, 2009;Clarke and Doel, 2005;Hallam, 2010;Virilio, 1989Virilio, , 2000 and spaces of being, becoming and 'being-toward' the world as existent space (Nancy, 1997: 7).…”
Section: Tropes Although Not Explicitly But Certainly Implicitly Olmentioning
confidence: 99%